Repressão aos "grupos de onze" na região norte do estado do Paraná (1963/1964) - Reggiani, João Paulo de Medeiros (2015)
This paper aims to analyze the formation of the "Groups of Eleven Companions" or "Nationalists Command", which were organized in the northern region of Paraná. The formation of the groups was designed by Leonel Brizola, and groups were formed in various parts of the country, in the final months of 1963. The groups were designed to support the Grassroots Reform, proposed by President João Goulart. The reforms envisaged a restructuring in the agrarian system, banking, urban and educational in Brazil. At the time filled with hope the brazilian populace, the sectors of greater conservatism of society looked with suspicion and fear for reforms. With the civil-military coup the new government initiated a strong repressive process from the early days of implementation of the scheme in april 1964. With the imposition of the Institutional Act 1 (AI-1) and the repressive apparatus to serve as a support to call "Operation Cleanup", people who before the coup supported the reforms proposed by João Goulart were considered enemies of the state and repressed by the new government. The "Operation Cleanup" materialized in the suspension of democratic rights, interventions unions, in purges of political, military purges in the military and civil service employees and also the establishment of hundreds of police-military investigations that found activities considered subversive across the country. Elected politicians or not, military, public officials, civilians, all those who presented some annoying to the new government, could be charged with a crime against the Order and Social Policy. In this context, has the purpose of considering the repressive action of the State in their ways and also meet people in the countryside were persecuted during the first moments of the military period. All citizens who have tuned the idea with movements belonging to the left were likely targets subject to repression and considered a threat to national security. Considering that the National Security Doctrine elected to the fore the enemy: people with sympathy or ideology directed to an opposition to the military government policy. Thus, the repressive system investigated and punished those considered subversive suspects the regime. Our interest is to analyze the persecution of the military regime to persons working with the so-called "Groups of Eleven Companions" in northern Paraná.